2019
DOI: 10.1016/j.ijcard.2018.11.127
|View full text |Cite
|
Sign up to set email alerts
|

Persistent atrial fibrillation: A systematic review and meta-analysis of invasive strategies

Abstract: Background: Persistent atrial fibrillation (AF) is associated with higher stroke and mortality risk than paroxysmal AF (pAF). Outcomes of catheter or surgical ablation are worse in patients with persistent AF than in pAF, and the optimal invasive rhythm control strategy has not been established. Purpose: We provide a contemporary systematic overview on efficacy and safety of catheter and minimallyinvasive surgical ablation for persistent AF. Methods: We systematically searched EMBASE, MEDLINE and CENTRAL from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 31 publications
0
36
0
12
Order By: Relevance
“…RFA is a commonly used minimally invasive interventional therapy strategy with high efficacy for patients with AF. 30 However, RFA also exposes patients to surgical risks owing to vascular puncture, catheter manipulation, and discharge for ablation. Besides being consistent with previous findings, our findings further confirm the safe application of RFA, despite known risks.…”
Section: Discussionmentioning
confidence: 99%
“…RFA is a commonly used minimally invasive interventional therapy strategy with high efficacy for patients with AF. 30 However, RFA also exposes patients to surgical risks owing to vascular puncture, catheter manipulation, and discharge for ablation. Besides being consistent with previous findings, our findings further confirm the safe application of RFA, despite known risks.…”
Section: Discussionmentioning
confidence: 99%
“…This case of APT highlights the potential for acute presentations occurring within 24 hours of amiodarone administration in patients with previous uneventful exposure. It also highlights the diagnostic challenges following cardiac ablation due to the range of differential diagnoses including pulmonary vein stenosis, a rare but serious complication which occurs in approximately 0.3%‐0.8% . What is unusual in this case is the rapidity of onset of pulmonary toxicity, within 1‐2 doses.…”
Section: Discussionmentioning
confidence: 78%
“…In a prospective evaluation of continuous warfarin therapy in stroke prevention after RF ablation, the COMPARE trial did not use clinical neurologists to assess patients as Victory AF did, and in the arm with uninterrupted VKA therapy reported a periprocedural stroke rate of 0% in patients with PersAF, and 0.49% in patients with long‐standing PersAF 11 . A large meta‐analysis of 56 catheter ablation studies, involving 7624 patients with persistent AF revealed a risk of thromboembolism of 0.7% 12 …”
Section: Discussionmentioning
confidence: 99%